Crisis management at AL-Shaheed Mohammed Yousif al –Najjar hospital from the perspective of it is employees - Al-Jazzar, Mohamed Noman Khalil; Al-Mughair, Mohammed Mohammed; Al-Agha, Mohammed Ramadan (Journal of Risk and Crisis Management, 2019)
This study aims to shed light on the crisis management at martyrMohammed Yousif Al Najjar Hospital from the point of view of its employees.The researcher used the analytical descriptive approach, where a questionnaire was designed to collect information from the sample.. Randomly chosen from the study community represented by directors, administrators, heads of departments and departments, in addition to 312 employees atmartyrMohammed Yousef Al Najjar Hospital. A sample of 12.5% ​​of the community was collected and 30 questionnaires were distributed and retrieved.The study found that there is a statistically significant relationship among the stages of the crisis management system and that there are no statistically significant differences among the average opinions of the sample members at the Martyr Mohammed Yousef Al-Najjar Hospital on the effectiveness of the crisis management system due to scientific qualification or gender,Because medical workers receive educational and cultural courses at the same level , And found that there were significant statistical differences among the average opinions of the respondents in the Martyr Mohammed Yousef Al-Najjar Hospital on the effectiveness of the crisis management system due to the functional category. The medical professions were the most aware of the effectiveness of crisis management and may be due to the university curriculum and specialized courses they receivedThe study recommended that the senior management of hospitals should provide the characteristics of a positive organizational culture that supports the readiness and readiness of the hospital for the potential crises and the ability to manage them, and to provide specialized courses for the employees and to take care of learning and taking lessons and lessons from previous crises.
Keywords: Crisis management; AL-Shaheed Mohammed Yousif al –Najjar hospital; Employees